2000
DOI: 10.1021/bi001443i
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Allosteric Activation of Yeast Pyruvate Kinase and Identification of Novel Effectors Using Computational Screening

Abstract: We have analyzed the structural determinants of the allosteric activation of yeast pyruvate kinase (YPK) by mutational and kinetic analysis and initiated a structure-based design project to identify novel effectors that modulate its allosteric response by binding to the allosteric site for fructose-1,6-bisphosphate (FBP). The wild-type enzyme is strongly activated by fructose-1,6-bisphosphate and weakly activated by both fructose-1-phosphate and fructose-6-phosphate; the strength of the activation response is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 27 publications
1
18
1
Order By: Relevance
“…The presence of a glutamic acid residue at this position was reported as an important property of unregulated PYK isoforms [33]. Moreover, for yeast PYK, it was experimentally shown that a mutation of threonine (T403) to glutamic acid at this structurally conserved position prohibits the allosteric activation of the enzyme by FBP [34].…”
Section: Resultsmentioning
confidence: 99%
“…The presence of a glutamic acid residue at this position was reported as an important property of unregulated PYK isoforms [33]. Moreover, for yeast PYK, it was experimentally shown that a mutation of threonine (T403) to glutamic acid at this structurally conserved position prohibits the allosteric activation of the enzyme by FBP [34].…”
Section: Resultsmentioning
confidence: 99%
“…K433 binds to the 6′-phosphate oxygen of FBP and is the only residue in the FBP-binding pocket that is different between PKM1 and PKM2 (Dombrauckas et al, 2005; Jurica et al, 1998). Substitution of an analogous FBP-binding residue in yeast PK (T403) by a negatively charged glutamate increased the dissociation constant (K D ) for FBP by 540-fold (Bond et al, 2000). Molecular modeling suggests that acetylation at K433, if it occurs, could significantly neutralize the charge on the lysine side chain, causing a steric hindrance of the FBP binding (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…The primary cause of PEP accumulation has been proposed to be the low activity of Pyk, which uses PEP as a substrate and is present in two isoforms in yeast cells. Pyk1 enzyme activity is stimulated by FBP [37] and Pka-mediated phosphorylation [38]; Pyk2 activity is not activated by FBP, and the gene expression of Pyk2 is subject to glucose repression [39]. Moreover, extremely low activity concomitant with a relatively high transcript level is characteristic of the Pyk2 enzyme [39].…”
Section: Discussionmentioning
confidence: 99%